2002
DOI: 10.1159/000049405
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 25 and 50 μg Vaginally Administered Misoprostol for Preinduction of Cervical Ripening and Labor Induction

Abstract: Our purpose was to compare the efficacy of 25 µg and 50 µg intravaginally administered misoprostol tablets for cervical ripening and labor induction. Either 25-µg (n: 58) or 50-µg (n: 56) misoprostol tablets were randomly administered intravaginally to 114 subjects with an unripe cervix for labor induction. The physician was blinded to the medication. Intravaginal misoprostol was given every 4 h until the onset of labor. The mean Bishop score before misoprostol administration was 2.1 ± 1.6 in the 25-µg group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
14
3
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
(22 reference statements)
9
14
3
3
Order By: Relevance
“…The proportion of women delivering within the first twelve hours and next twelve hours of induction were similar among the groups, which is consistent with the finding by other investigators [14,17]. This is contrast to the finding of Meydanli et al [19] and Elhassan et al [17] Meydanli reported that more women delivered between 12-24 hours in the 25 µg group while El-hassan reported that fewer delivered vaginally in the 25 µg group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The proportion of women delivering within the first twelve hours and next twelve hours of induction were similar among the groups, which is consistent with the finding by other investigators [14,17]. This is contrast to the finding of Meydanli et al [19] and Elhassan et al [17] Meydanli reported that more women delivered between 12-24 hours in the 25 µg group while El-hassan reported that fewer delivered vaginally in the 25 µg group.…”
Section: Discussionsupporting
confidence: 89%
“…There was no statistical significant difference between the two misoprostol regimens in terms of clinical efficacy. Although the study found that induction delivery interval was similar among the two groups, other investigators [13][14][15][16][17][18] had demonstrated that it was shorter in the 50 µg group. In a meta-analysis comparing 25 µg with 50 µg misoprostol, the induction vaginal delivery interval was nearly five hours shorter in the 50 µg group [19].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In a comparative study reported by Has et al showed the rate of Cesarian Section due to fetal distress was higher with higher dose (28.6 vs. 10.3% p>0.05). 5 This was comparable to our study (group B 20 % vs group A 16%). We observed that the incidence of normal contraclity pattern (tachysystole, hyperstumulation) was higher in 50 g (24% vs 14%, p>0.05%) was comparable with study by Sanchez-Ramos et al 6 Minor side effects were common with higher dose but uterine Rupture did not occur in both groups in our study.…”
Section: Resultssupporting
confidence: 91%
“…Babies with low Apgar score, requiring admission were significantly higher in 50 g group. This was in concurrence with the observations made by Has et al 5 Contrary to this Sanchez-Ramos et al in their meta-analysis of five randomize clinical trials reported comparable neonatal outcomes with the two doses.…”
Section: Resultssupporting
confidence: 89%